Answer:
The product of a constant factor of six and a factor with the sum of two terms
Step-by-step explanation:
Answer: C
Step-by-step explanation: I took the quiz and they said it was correct
Answer:
The answer is (-4/3)
Step-by-step explanation:
3(x − 4) = 12x
Multiply (x – 4) by 3 we get,
3(x – 4) = 12x
3x – 12 = 12x
3x – 12x – 12 + 12 = 12x – 12x + 12
-9x = 12
-9x/(-9) = -12/9
x = -4/3
Thus, The value of x is -4/3
<u>-TheUnknownScientist 72</u>
The answer should be 2(2b+3)
Hello you answer will be...... -x+4
let me know if I’m right